1999
DOI: 10.1070/qe1999v029n04abeh001490
|View full text |Cite
|
Sign up to set email alerts
|

ComplexABCDtransformations for optical ring cavities with losses and gain

Abstract: We propose a new design concept and a fabrication process for three-dimensional (3D) silicon photonic crystals on a 100 nm scale that does not require any alignment processes. The elemental technique used in this process is two directional electrochemical etching processes at a particular magnetic field. First, we have performed photonic band calculation and estimated device parameters to obtain the maximum photonic band gap in the visible range centered at around 800 nm. Next, we have experimentally observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the presence of losses, the elements of matrices T (4) become complex; however, the matrices themselves remain unimodal, as in the case of perfect resonators [1]. A more general analysis of complex transformations in the mechanics of narrow beams has been performed by Maslov [5], who has shown that, if we have a beam, field asymptotic (1) remains correct in the complex case.…”
Section: Basic Formulas: Equation For the Resonator's Natural Oscillamentioning
confidence: 96%
See 3 more Smart Citations
“…In the presence of losses, the elements of matrices T (4) become complex; however, the matrices themselves remain unimodal, as in the case of perfect resonators [1]. A more general analysis of complex transformations in the mechanics of narrow beams has been performed by Maslov [5], who has shown that, if we have a beam, field asymptotic (1) remains correct in the complex case.…”
Section: Basic Formulas: Equation For the Resonator's Natural Oscillamentioning
confidence: 96%
“…(5) must have solutions with a negative (positive) imaginary part. For passive resonators, this condition is sufficient because, in such resonators, the sign of parameter Im H is retained along the beam [1]. In order to solve Eq.…”
Section: Basic Formulas: Equation For the Resonator's Natural Oscillamentioning
confidence: 98%
See 2 more Smart Citations